Crohn’s Disease and the Melkersson-Rosenthal Syndrome - Alexandra Ilnyckyj; Thomas AM Aldor; Richard Warrington; Charles N Bernstein (Canadian Journal of Gastroenterology)
A 30-year-old woman with a 10-year history of recurrent bloody diarrhea and documented colitis of the descending colon, consistent with Crohn’s disease, presented with an exacerbation of her gastrointestinal disease and an 18-month history of recurrent facial and genital swelling. Her course evolved to include severe ear pain, dysphagia and colonic dysmotility. She was diagnosed with Melkersson-Rosenthal syndrome and treated with multiple agents. The neurological aspects of her presentation are highlighted, and the Melkersson-Rosenthal syndrome is reviewed.